The role of salt abuse on risk for hypercalciuria - Damasio, Patricia C. G. [UNESP]; Amaro, Carmen R. P. R. [UNESP]; Cunha, Natalia B. [UNESP]; Pichutte, Ana C. [UNESP]; Goldberg, José [UNESP]; Padovani, Carlos Roberto [UNESP]; Amaro, João Luiz [UNESP] (Biomed Central Ltd., 2011)
Background: Elevated sodium excretion in urine resulting from excessive sodium intake can lead to hypercalciuria and contribute to the formation of urinary stones. The aim of this study was to evaluate salt intake in patients with urinary lithiasis and idiopathic hypercalciuria (IH).Methods: Between August 2007 and June 2008, 105 lithiasic patients were distributed into 2 groups: Group 1 (n = 55): patients with IH (urinary calcium excretion > 250 mg in women and 300 mg in men with normal serum calcium); Group 2 (n = 50): normocalciuric patients (NC). Inclusion criteria were: age over 18 years, normal renal function (creatinine clearance >= 60 ml/min), absent proteinuria and negative urinary culture. Pregnant women, patients with intestinal pathologies, chronic diarrhea or using corticoids were excluded. The protocol of metabolic investigation was based on non-consecutive collection of two 24-hour samples for dosages of: calcium, sodium, uric acid, citrate, oxalate, magnesium and urinary volume. Food intake was evaluated by the three-day dietary record quantitative method, and the Body Mass Index (BMI) was calculated and classified according to the World Health Organization (WHO). Sodium intake was evaluated based on 24-hour urinary sodium excretion.Results: The distribution in both groups as regards mean age (42.11 +/- 10.61 vs. 46.14 +/- 11.52), weight (77.14 +/- 16.03 vs. 75.99 +/- 15.80), height (1.64 +/- 0.10 vs. 1.64 +/- plusorminus 0.08) and BMI (28.78 +/- 5.81 vs. 28.07 +/- 5.27) was homogeneous. Urinary excretion of calcium (433.33 +/- 141.92 vs. 188.93 +/- 53.09), sodium (280.08 +/- 100.94 vs. 200.44.93 +/- 65.81), uric acid (880.63 +/- 281.50 vs. 646.74 +/- 182.76) and magnesium (88.78 +/- 37.53 vs. 64.34 +/- 31.84) was significantly higher in the IH group (p < 0.05). There was no statistical difference in calcium intake between the groups, and there was significantly higher salt intake in patients with IH than in NC.Conclusions: This study showed that salt intake was higher in patients with IH as compared to NC.